Hambatan Dan Standar Pelayanan Publik Pada Pemerintah Daerah - Nur Maria Magdalena; Steviana Br. Sihombing; Mellyana Candra (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Public services according to Law Number 25 of 2009 concerning Public Services are activities or series of activities in order to fulfill service needs in accordance with statutory regulations for every citizen and resident for goods, services, and / or administrative services provided by public service providers. In Indonesia, there are development problems that become obstacles in realizing good and adequate public services, the first is the bureaucracy that is fat, slow, and unable to provide excellent service to the public and investors, the second is corruption, where there are still many state administrators who abuse their positions and manage state finances, and the third or last is the problem of inadequate infrastructure and the lack of a state budget for its development and maintenance. Service standards are benchmarks used as guidelines for service delivery and reference for assessing service quality as an obligation and promise of the government to the community in the context of quality service.